Sensing of intracellular Hcp levels controls T6SS expression in Vibrio cholerae - Manera, Kevin; Caro, Florence; Li, Hao; Pei, Tong-Tong; Hersch, Steven J.; Mekalanos, John J.; Dong, Tao G. (Proceedings of the National Academy of Sciences - PNAS, 2021)
The type 6 secretion system (T6SS) is a bacterial weapon broadly distributed in gram-negative bacteria and used to kill competitors and predators. Featuring a long and double-tubular structure, this molecular machine is energetically costly to produce and thus is likely subject to diverse regulation strategies that are largely ill defined. In this study, we report a quantity-sensing control of the T6SS that down-regulates the expression of secreted components when they accumulate in the cytosol due to T6SS inactivation. Using Vibrio cholerae strains that constitutively express an active T6SS, we demonstrate that mRNA levels of secreted components, including the inner-tube protein component Hcp, were down-regulated in T6SS structural gene mutants while expression of the main structural genes remained unchanged. Deletion of both hcp gene copies restored expression from their promoters, while Hcp overexpression negatively impacted expression. We show that Hcp directly interacts with the RpoN-dependent T6SS regulator VasH, and deleting the N-terminal regulator domain of VasH abolishes this interaction as well as the expression difference of hcp operons between T6SS-active and inactive strains. We find that negative regulation of hcp also occurs in other V. cholerae strains and the pathogens Aeromonas dhakensis and Pseudomonas aeruginosa. This Hcp-dependent sensing control is likely an important energy-conserving mechanism that enables T6SS-encoding organisms to quickly adjust T6SS expression and prevent wasteful build-up of its major secreted components in the absence of their efficient export out of the bacterial cell.